Combined application of organic and inorganic fertilizer on Alfisol soil fertility and maize growth. Issue 1 (July 2021) - Syamsiyah, J; Herdiansyah, G; Aisyah, N; Mentari, F C; Larasati, I
Abstract: Fertilizer is an important factor in crop production, but its effectiveness depends on climate and the balance of fertilizers applied. This research aim was to determine the potential use of organic fertilizers to reduce the use of inorganic fertilizers on the growth of maize and Alfisol soil fertility. This research was conducted in the Jumantono, Karanganyar, used the Randomized Block Design with 9 treatments (A = Control, B = NPK standard, C = ¼ NPK + 1 PO, D = ½ NPK + 1 PO, E = ¾ NPK +1 PO, F = 1 NPK + 1 PO, G = ¾ NPK + ¼ PO, H = ¾ NPK + ½ PO, I = ¾ NPK + ¾ PO).The results showed that organic fertilizers at doses ¼, ½ and ¾ accompanied by ¾ NPK standard gives N total, P total, K total, and the plant height, number of leaves and stem diameter which are not different with dose of NPK standard. Organic fertilizers can reduce the use of NPK fertilizers.